Pengaruh Keterampilan Dasar Mengajar Guru Terhadap Hasil Belajar PAI Siswa Kelas VIII SMP PGRI 8 Denpasar Tahun Pelajaran 2020/2021 - Cahyati, Nur; Soedjiwo, Novena Ade Fredyarini; Dinansyah, Dinansyah (STAI Denpasar Bali, 2023)
The teaching skills of a teacher in learning are one of the important components that must be possessed by a teacher in carrying out learning activities which will be very decisive in the process of achieving learning outcomes for students. on PAI learning outcomes for grade VIII SMP PGRI 8 Denpasar in the 2020/2021 academic year. 2) The contribution of basic teaching skills for teachers to PAI learning outcomes for class VIII SMP PGRI 8 Denpasar in the 2020/2021 academic year. This research uses correlational quantitative research. Data collection techniques used in this research is to use questionnaires, observation and documentation. The results showed that: 1) There was a significant positive effect on the basic skills of teaching teachers to PAI learning outcomes for class VIII SMP PGRI 8 Denpasar, it is known that tcount > ttable is 4.107 > 1.687, so Ho is rejected and Ha is accepted, meaning that the correlation coefficient is significant. /significant 2) The variable of basic teaching skills of teachers (X) has a simultaneous contribution of 32.5% to the learning outcome variable (Y) which is classified as low and the remaining 67.5 is influenced by other factors not examined by the author.